Volatile Compound-Mediated Recognition and Inhibition Between Trichoderma Biocontrol Agents and Fusarium oxysporum - Li, Ningxiao; Alfiky, Alsayed; Wang, Wenzhao; Islam, Md; Nourollahi, Khoshnood; Liu, Xingzhong; Kang, Seogchan (Frontiers in Microbiology, 2018)
Certain Trichoderma strains protect plants from diverse pathogens using multiple mechanisms. We report a novel mechanism that may potentially play an important role in Trichoderma-based biocontrol. Trichoderma virens and T. viride significantly increased the amount/activity of secreted antifungal metabolites in response to volatile compounds (VCs) produced by 13 strains of Fusarium oxysporum, a soilborne fungus that infects diverse plants. This response suggests that both Trichoderma spp. recognize the presence of F. oxysporum by sensing pathogen VCs and prepare for attacking pathogens. However, T. asperellum did not respond to any, while T. harzianum responded to VCs from only a few strains. Gene expression analysis via qPCR showed up-regulation of several biocontrol-associated genes in T. virens in response to F. oxysporum VCs. Analysis of VCs from seven F. oxysporum strains tentatively identified a total of 28 compounds, including six that were produced by all of them. All four Trichoderma species produced VCs that inhibited F. oxysporum growth. Analysis of VCs produced by T. virens and T. harzianum revealed the production of compounds that had been reported to display antifungal activity. F. oxysporum also recognizes Trichoderma spp. by sensing their VCs and releases VCs that inhibit Trichoderma, suggesting that both types of VC-mediated interaction are common among fungi.